Understanding Buy-Now-Pay-Later Adoption in the Muslim Market: Do Religious-Based Ethics Matter? - Sutikno, Bayu; Aji, Hendy Mustiko (The South East Asian Journal of Management, 2024)
Research Aims: This study aims to investigate the relationship between religious-based ethics and trust in the Buy-Now-Pay-Later system on its adoption among Muslim consumers in Indonesia. Further, it examines the moderating role of perceived BNPL benefits. Design/Methodology/Approach: 448 usable responses were collected for this study. Partial least squares structural equation modelling (PLS-SEM) was used to test the research model, encompassing mediation and moderation analyses. Research Findings: This study reveals that the perceived riba risk exerts a negative influence on trust in the BNPL mechanism and its adoption within the Muslim market. However, the negative effect on the adoption of BNPL is significantly moderated by the perceived BNPL benefits and mediated by trust in the BNPL mechanism. This suggests that, while concerns about riba pose a barrier, highlighting the benefits and building trust in the BNPL mechanism can mitigate these concerns and encourage adoption. Theoretical Contribution/Originality: This study contributes to the literature by clarifying how perceived religious-based ethics influence the adoption of BNPL in Muslim markets. Managerial Implication in the South East Asian Context: By demonstrating a deep understanding of the religious-based ethics surrounding BNPL, providers, especially in the South East Asian region, can unlock significant growth potential and contribute positively to the inclusion of financial technology. Research Limitation & Implications: This study highlights the influence of religious-based ethics on consumer behaviour without investigating the dynamics between seeking novelty and feeling sinful (guilty). Future research should explore how Muslim consumers' curiosity and guilt affect the adoption of BNPL.